2021
DOI: 10.3390/brainsci11030405
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of TMS and TMS-EEG to the Understanding of Mechanisms Underlying Physiological Brain Aging

Abstract: In the human brain, aging is characterized by progressive neuronal loss, leading to disruption of synapses and to a degree of failure in neurotransmission. However, there is increasing evidence to support the notion that the aged brain has a remarkable ability to reorganize itself, with the aim of preserving its physiological activity. It is important to develop objective markers able to characterize the biological processes underlying brain aging in the intact human, and to distinguish them from brain degener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 198 publications
(317 reference statements)
0
10
0
Order By: Relevance
“…Taken together, these findings suggest a possible effect of COVID-19 syndrome on cortical transmission which might be objectively measured by neurophysiological techniques. Indeed, the association between cortical excitability measured by TMS and brain oscillatory activity measured by EEG has been reported in physiological brain aging and in different neurological diseases, including epilepsy and MCI [29][30][31].…”
Section: Discussionmentioning
confidence: 96%
“…Taken together, these findings suggest a possible effect of COVID-19 syndrome on cortical transmission which might be objectively measured by neurophysiological techniques. Indeed, the association between cortical excitability measured by TMS and brain oscillatory activity measured by EEG has been reported in physiological brain aging and in different neurological diseases, including epilepsy and MCI [29][30][31].…”
Section: Discussionmentioning
confidence: 96%
“…Increasing the age limit of enrollment may increase participation in the study, in particular of W patients and of women, as these groups presented at a later age with stroke. Brain plasticity is diminishing with advancing age 41,42 ; however, evidence for life-long neuroplasticity is mounting, 43,44 suggesting that older patients might also benefit from an effective non-invasive stimulation. Enrolling patients with hemorrhagic strokes and severe UE weakness could preferentially enhance the participation of men.…”
Section: Discussionmentioning
confidence: 99%
“…Next, 120 paired-pulse TMS stimuli were delivered to the left-M1 at random intervals between 3 and 6 s. The intensities of both pulses were applied at 120% of RMT, and the ISI was 100 ms, selecting this interval because it was reportedly optimal ( Sanger et al, 2001 ), and previous research has suggested age-related changes at it ( McGinley et al, 2010 ; Opie et al, 2015 , 2018 ). From this stimulation, LICI was calculated using the following formula ( Guerra et al, 2021 ):…”
Section: Methodsmentioning
confidence: 99%
“…BBHI, Barcelona Brain Health Initiative; NP, Neuropsychological assessment; MRI, Magnetic resonance imaging; RMT, Resting Motor Threshold. 10.3389/fpsyg.2022.998062 Frontiers in Psychology 04 frontiersin.org stimulation, LICI was calculated using the following formula (Guerra et al, 2021):…”
Section: Tms Protocolmentioning
confidence: 99%
See 1 more Smart Citation